A Study on Sustainable Hospital Supply Chain Management towards Societal Advancement in the Post-Pandemic Era - Shaiful Islam; Md. Mamun Habib; Gazi Md Nurul Islam (ExcelingTech, 2023)
Abstract— This study delves into the intricate relationships between Hospital Infrastructure Development (HID), Collaboration Information Flow (CIF), Forecasting and Planning Management (FPM), Technology Supply Chain Application (TSCA), Sustainable Hospital Supply Chain Management (SHSCM), and Sustainable Societal Advancement (SSA) within the healthcare sector of Bangladesh. Utilizing a structured questionnaire, data was collected from a diverse group of 22 respondents, including doctors, administrators, and patients. Frequencies Analysis, conducted using IBM SPSS, provided a comprehensive demographic overview, while the Alpha Cronbach test affirmed the reliability of the research instrument with a high value. The fitness index analysis, performed using IBM AMOS software, subsequent modifications based on the Modification Index (MI) results led to a model that closely met the criteria of CMIN, degrees of freedom (df), CMIN/df, incremental fit CFI IFI, and absolute fit RMSEA, underscoring the pivotal role of the aforementioned variables in enhancing SHSCM and contributing to SSA. The findings emphasize the significance of a robust healthcare supply chain in ensuring optimal healthcare delivery and broader societal benefits. This research offers valuable insights for healthcare administrators, policymakers, and stakeholders, providing a roadmap for building resilient, efficient, and sustainable healthcare systems in the post-pandemic era.Keywords—Sustainable Hospital Supply Chain Management (SHSCM), Sustainable Societal Advancement (SSA), IBM SPSS, IBM AMOS.